Development of an ethnoscience-based teaching module on states of matter and their changes to enhance elementary students’ scientific literacy - Samsiah, Samsiah; Sudarmin, Sudarmin; Widiarti, Nuni (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
This study aims to develop an ethnoscience-based science teaching module on the forms of matter and their changes to improve elementary school students’ scientific literacy, as well as to determine its characteristics, feasibility, effectiveness, and practicality. The research employed a Research and Development (R&D) design using the 4D model proposed by Thiagarajan, Semmel, and Semmel, consisting of the Define, Design, Develop, and Disseminate stages. The module integrates local cultural knowledge from Bangka—such as traditional foods including martabak, jongkong cake, and es jeruk kunci—to contextualize scientific concepts for young learners. The results show that the developed module meets high validity standards, with Aiken’s V values of 0.88 for material experts, 0.86 for language experts, and 0.85 for media experts, all categorized as “very valid.” Effectiveness testing revealed an N-gain score of 0.80 (80%), indicating an effective improvement in students’ scientific literacy. Practicality assessments also demonstrated excellent results, with teacher responses averaging 95.31% and student responses 97.50%, both categorized as “very practical.” These findings indicate that the ethnoscience-based teaching module is valid, effective, and practical for enhancing scientific literacy in elementary school science learning.